PENGARUH WARNA WADAH PEMELIHARAAN TERHADAP PENINGKATAN INTENSITAS WARNA IKAN GUPPY (Poecilia reticulata) - Dimas Rizki Pratama; Henni Wijayanti; Herman Yulianto (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2018)
Guppy is one of the most popular ornamental fish. In some ornamental fish, colour of aquarium can enhance the fish colour intensity. The research aims to determine the effect of different aquarium colour on Guppy colour intensity which maintenance on semi outdoor. The research was used completely Randomized Design (CRD) with 4 treatments and 3 replications (maintenance guppy in colourless aquarium, black coloured aquarium, yellow coloured aquarium, silver coloured aquarium). The Guppy fish used is 60 days old that kept on aquarium 30 cm x 20 cm x 30 cm and the water volume is 4 liters/aquarium. Research was conducted for 40 days, fish amount is 8 fish/aquarium. Colour intensity data were analyzed by using ANOVA and the significantly different results followed by a further test of Least Significant Difference (LSD). Observed parameters were the colour intensity, pH, and temperature. The results showed that maintenance Guppy fish under different colour of aquarium gave the effect on Guppy colour intensity, the best effecton colour intensity Guppy fish show at the colourless aquarium.